Ethics of local government heads: A study of leadership in Surabaya, Bandung, and Purwakarta, Indonesia - Mohammad Taufik; Bambang Irawan; Etika Khairina; Mochammad Iqbal Fadhlurrohman; Paisal Akbar (Faculty of Social and Political Science, Universitas Airlangga, 2021)
The most significant aspect of a leader’s behavior is ethics because it is a guideline for interacting, acting, and involving in government in an ethical manner without abusing power. This article aims to find out how the ethics of regional heads are applied in the administration of regional government. The research method used was qualitative with a literature study approach. Data collection was done by literature study by collecting various materials from books, journals, research results, and mass media (news). The results of research conducted on three districts/cities in Indonesia involving three leaders of the Mayor of Surabaya, the Mayor of Bandung, and the Regent of Purwakarta in 2015 show some real examples of regional heads who apply ethical values in their leadership, which can be seen from their performance and competence as well as ideas (innovation) and relationships with the community. It has gone well by applying ethical principles in its performance such as accountability, transparency, legal assurance, and justice. Competence in leadership includes the application of ethical values including emotional intelligence, self-management, social awareness, and relationship management. This study concludes that government ethics greatly influence the implementation and desired results, as well as on leadership, which will affect the performance carried out.